Pulmonary Endarterectomy in Latvia: A National Experience - Matiss Sablinskis; Kristaps Sablinskis; Andris Skride (Medicina, 2019)
Background and objectives: Chronic thromboembolic pulmonary hypertension (CTEPH) is a hemodynamic state characterized by chronic obstruction in pulmonary circulation. The treatment of choice is pulmonary endarterectomy (PEA). The aim of our study was to compile and analyze the data of a small, national center, which has not yet been done in the Baltic states. Materials and methods: The data of Latvian CTEPH registry in timeframe from 1 September 2007 to 31 December 2016 was retrospectively analyzed and all patients who underwent PEA were included. Results: PEA was done for 7 patients. The in-hospital mortality was 14%. The 3-year survival rate was 86%. The procedure restored pulmonary blood pressure to normal values for three of the patients (42%). The remaining four patients (57%) had persistent pulmonary hypertension (mPAP > 30 mmHg), which required continuous therapy. There was a comparable decline in mean mPAP compared to baseline, 53.4 ± 14.4 mmHg to 44.3 ± 30 mmHg, respectively. At 12-month follow-up, there was a significant improvement in functional capacity, as seen by increased 6-min walk test distance and shifts in New York Heart Association functional class. Conclusions: Only 16% of all prevalent Latvian CTEPH patients have underwent PEA in the course of nine years, despite it being the treatment of choice for CTEPH. As PEA and other emerging treatment options, such as balloon pulmonary angioplasty, can only be done in expert centers, numerous organizational, logistical, and economic issues arise for patients of smaller countries, where such centers have not yet been created due to lack of experience and limited amount of patients.